Metagenomic analysis of endemic viruses in oral secretions from Chinese pigs. Issue 5 (1st September 2022) - Umar, Sajid; Anderson, Benjamin D.; Chen, Kuanfu; Wang, Guo‐Lin; Ma, Mai‐Juan; Gray, Gregory C.
Abstract: Background: Pigs are unique reservoirs for virus ecology. Despite the increased use of improved biosecurity measures, pig viruses readily circulate in Chinese swine farms. Objectives: The main objective of this study was to examine archived swine oral secretion samples with a panel of pan‐species viral assays such that we might better describe the viral ecology of swine endemic viruses in Chinese farms. Methodology: Two hundred ( n  = 200) swine oral secretion samples, collected during 2015 and 2016 from healthy pigs on six swine farms in two provinces in China, were screened with molecular pan‐species assays for coronaviruses (CoVs), adenoviruses (AdVs), enteroviruses (EVs), and paramyxoviruses (PMV). Samples were also screened for porcine circovirus (PCV) 3, porcine reproductive and respiratory syndrome virus (PRRSV) and influenza A virus (IAV). Results: Among 200 swine oral secretion samples, 152 (76.0%) were found to have at least one viral detection. Thirty‐four samples (17%) were positive for more than one virus, including 24 (70.5%) with dual detection and 10 (29.5%) with triple detection. Seventy‐eight (39.0%) samples were positive for porcine AdVs, 22 (11.0%) were positive for porcine CoVs, 21 (10.5%) were positive for IAVs, 13 (6.5%) were positive for PCV, 7 (3.5%) were positive for PMV, six (3.0%) were positive for PRRSV and five (2.5%) were positive for porcine EV. Conclusion: Our findings underscore the high prevalence of numerous viruses among production pigs in China and highlight the need for routine, periodic surveillance for novel virus emergence with the goal of protecting pigs. Abstract : Pigs are unique animal reservoirs for pathogen transmission. Coinfections are more frequent in pig farms than single infections.